Language learners’ identities in EFL settings: resistance and power through discourse - Gómez Lobatón, July Carolina (Colombian Applied Linguistics Journal, 2012)
This research project aims at identifying and analyzing different identities students construct as learners of a foreign language when interacting within an EFL classroom, and how this identity construction might have possible effects on students’ language learning process. This study, which was carried out with undergraduate students from a private university in Bogotá, was the product of permanent observation to the development of students language learning process (specially speaking skill) and how the implicit or explicit student-teacher interaction might constitute an important element to this development, relies under the principles of CCDA (Critical Classroom Discourse Analysis). The idea of implementing this research methodology has to do with the need of looking beyond fixed categorizations and rather listen to how learners negotiate different identities as they employ diverse cultural and linguistic resources to construct knowledge in classrooms. Throughout the process of data collection, with transcripts of oral interactions undertaken in the classroom and interviews to students as main sources of analysis, a new perspective of pupils as social actors who hold multiple social identities was discovered. The results show that issues such as the use of L1 in the EFL classroom, the teacher‘s conception of language learning and teaching and the silent fight for power among teacher and students constitute important elements in the struggle of students when constructing their social and individual identities as learners within a given classroom community.